Lipid Indices vs Anthropometric Indices in Metabolic Syndrome and Type 2 Diabetes Mellitus - Augusthy, Asha; Sahu, Suchanda; Jeppu, Ashok Kumar (Annals of Pathology and Laboratory Medicine, 2021)
Background: Diabetes mellitus is a metabolic disease known by chronic hyperglycemia which results from defective insulin action and secretion. Metabolic Syndrome consists of a constellation of metabolic abnormalities that confer increased risk of diabetes mellitus. The aim of our study is to find out whether non-invasive, clinically measurable surrogates could be useful in identifying body fat distribution and help predict metabolic syndrome and diabetes risk and to compare the performance of anthropometric indices with lipid indices in identifying metabolic syndrome and diabetes. Methods: 50 individuals with metabolic syndrome ,50 individuals with type 2 diabetes mellitus and 50 controls were selected by purposive sampling technique. For cases and controls history was taken, physical examination was done .Fasting blood sugar, Serum High density lipoprotein and Serum Triglyceride levels were estimated. Body mass index, a body shape index, visceral adiposity index, lipid accumulation factor was calculated. Results: The mean values visceral adiposity index, lipid accumulation factor were significantly increased (p<0.001) in cases compared to controls. Conclusion: Our study concluded that lipid indices visceral adiposity index, lipid accumulation factor is better than anthropometric indices like body mass index, a body shape index in predicting metabolic syndrome and type 2 diabetes mellitus. Anthropometric indices when used should be correlated with metabolic variables and clinical symptoms.